THERMOPHYSICAL PROCESSES AT RECEIPT OF MICROGRANULS BY GAS - Ternovyi , Yurii; Panova , Natalii (Scientific Journal "Metallurgy", 2020)
When a liquid metal jet is sprayed with a gas stream, the resulting two-phase gas-liquid and gas-solid systems form a metal-gas torch in which the gas stream interacts with the melt, which essentially determines the size and shape of the particles of the obtained powder. The article analyzes various approaches and methods for calculating cooling rates during gas spraying. It is shown that the calculation of the cooling rate during crystallization depends on the particle size and the presence of satellites on their surface. When solving the unsteady Stefan problem, the temperature fields in the sprayed particles at any point on the trajectory, as well as the dimensions of the spraying chamber, were correctly calculated. The heat transfer problems were solved before crystallization and during crystallization by the example of nickel melt under argon sputtering conditions. So, when spraying particles d ≤ 50 μm, the thermal energy of the droplet is concentrated at the "geometric point", the size of the vertical chamber is 0.21 m, and the cooling rate of the sprayed particles, which is about 7.104 K / s before crystallization, has a unique relationship with dendritic parameter. In the formation of individual large granules (d > 100 μm) with satellites, calculations of heat transfer processes require refinement - such particles are cooled faster than large particles, but without satellites, due to the incorporation of granules of crystallized (colder) satellites into the body of the granule and sticking to its surface total mass of 5-10% relative to the mass of the main drop. In this case, the development of several different crystallization processes takes place. Simultaneously with internal homogeneous crystallization, the process of external homogeneous crystallization takes place, in which colder solid satellites welded to the surface play the role of crystallization centers. This leads to the fact that the solidification of such particles occurs in a shorter time and the length of the vertical tracks of the particles decreases in this case by about 10%. Thus, the solution of the problem allows one to calculate correctly particle tracks and sizes when designing spraying plants, which ensure full crystallization of spherical particles of different sizes.